Antimicrobial Resistance pattern of Common Bacterial Pathogens in Tertiary Care Hospitals in Dhaka City (Bangladesh Journal of Medical Microbiology, 2013)
Bacterial pathogens were isolated from  pus, wound swab, urine, blood and throat swab. A total  of 300 samples were collected from Sir Salimullah Medical College & Mitford Hospital (SSMC & MH), BIRDEM and National Medical College (NMCH) and processed following standard microbiological methods. Antibiotic susceptibility testing were performed on pure culture isolates by employing Kirby-Bauer disc-diffusion method for the commonly used antibiotics. 326 (93.33%) bacterial pathogens were isolated from 300 patients. Single bacterial pathogen was present in 78% cases and mixed bacterial pathogens were in 15.40% cases.  Staphylococcus aureus was the predominant species (38.66%) followed by Escherichia coli (38%), Pseudomonas spp. (13.33%), Proteus spp. (8.33%), CoNS (7.66%), Serratia spp (2.85%), Klebsiella spp. (2.00%) and  Acinetobacter spp. (0.97%). Resistance rate towards amoxicillin, ciprofloxacin, co-trimoxazole and  ceftriaxone were high among both Gram-positive and Gram-negative isolates. However, both groups showed good susceptibility to gentamicin and levofloxacin. S. aureus and CoNS showed 100% sensitivity to vancomycin and all isolated Gram negative organisms showed 98-100% sensitivity to imipenem.These results indicate that gentamicin and levofloxacin may be convenient alternative antimicrobial agent for both Gram-positive and Gram-negative bacteria and vancomycin for Gram positive and imipenem for Gram negative bacteria as well.DOI: http://dx.doi.org/10.3329/bjmm.v7i2.19327 Bangladesh J Med Microbiol 2013; 07(02): 13-16